REKONSTRUKSI HUKUM PIDANA ISLAM (Upaya Reformulasi Teori Hukuman berdasarkan Legal Reasoning Pemidanaan dalam Islam) - Ahmad Faisal (DIKTUM: Jurnal Syariah dan Hukum, 2015)
Cutting off of hands and feet, crucifixion, death penalty and flogging is a typical shape for Islamic criminal offence. If it form of punishment imposed, it gives a terrible impression on the public. The problem is, whether the ways these penalties are fixed and must be impelemented in accordance with instructions verses of the Koran and the Sunnah of the Prophet, or in fact made possible a change in the form of punishment which was originally focused on physical abuse to torture that is non-physical. In this context required a reconstruction effort. This reconstruction must be interpreted. Arkoun views, the reason for the anactment of the law of Islamic criminal law was to determine the causes behind the birth of the Islamic criminal law formulation in the form as it is known today.